Tuning up! The Innovative Potential of Musikvermittlung - Chaker, Sarah; Petri-Preis, Axel (2022)
Professional musicians who perform in hospitals, retirement homes and prisons, creatively stimulated by the residents; babies crawling over exercise mats, enjoying classical music together with their parents; concert-goers who take their seats between the musicians in order to experience music up close with all their senses - the opportunities to make and experience music are almost unlimited. Various actors in the field of classical music have taken this as a chance to develop a wide range of new artistic and educational practices over the last two decades, aiming to facilitate in-depth aesthetic experiences, to diversify and bond with audiences and to encourage active cultural participation. The contributors focus on the innovative potential of Musikvermittlung as a social bridge-builder for concert life, (higher) music education, research and social life.